DETERMINANTS AND PATTERN OF POSTPARTUM PSYCHOLOGICAL DISORDERS IN HAZARA DIVISION OF PAKISTAN - Irfan, Naveed; Badar, Ahmed (Journal of Ayub Medical College Abbottabad, 2003)
Background: The risk of psychological disorders in women increases during the postpartum period. The major forms of these disorders are post partum psychoses and post partal depression. This study was designed to evaluate the presentation and sociodemographic characteristics of postpartal psychological disorders at Hazara division of Pakistan. Methods: This study was carried out over a period of three years at three major cities of Hazara, Pakistan. One psychiatry clinic in each of these cities was selected and record of all the psychiatric patients was kept. All the patients presenting with post partal disorders were included in the study. A proforma was used to collect information about a wide variety of sociodemographic variables and presentation of disease. Frequencies were calculated for different variables. Results: 8.66 % (1248) out of 14,400 patients of psychiatric disorders presented with post partal disorders. 60 % out of these 1248 had post partal psychoses while the rest had post partal depression. The majority of our patients with post partal depression were young (20-31years), illiterate (80%), having past history of psychoses/depression (70%), house wives (95%), from rural areas (65%), highly religious (60%), poor (90%), with husband away for job etc. (70%), primipara (80%) and with a live baby born (70%). A number of stressors were identified in 65 % of subjects. Conclusions: There is a predictable set of risk factors for post partal psychological disorders in the population of Hazara. Proper identification of these risk factors during antenatal period with collaboration of obstetrician and psychiatrist can reduce the morbidity associated with this group of disorders. Keywords: Post Partal Psychoses, Post Partal Depression, Postpartum psychological disorders,